MECHANOKINESITHERAPY IN REHABILITATION OF INDUSTRIAL INJURIES - Раиса Васильевна Гордеева; Ольга Васильевна Кузьменко; Сергей Николаевич Филимонов; Татьяна Ивановна Анищенкова (Медицина в Кузбассе)
The method for the speeded-up restoration of the movements in the injured joints, which raises the range of motions in a short time, quickly relieving a painful syndrome, warning the development of dystrophic changes in the musculoskeletal system has been offered.